Meta-analysis : RME impact on critical thinking skills of junior high school students - Nurintya, Fairuz Hanan; Scolastika Mariani; Arief Agoestanto; Sugiman (Pusat Studi Pengembangan Pembelajaran Matematika, 2024)
Critical thinking is an ability needed in facing revolution 4.0 and society 5.0, so it is important for students to be equipped with these abilities. PISA results and previous studies results show that students critical thinking skills are still low, so a learning approach is needed to improve them. The purpose of this study is to determine the effect of Realistic Mathematics Education (RME) on critical thinking skills of junior high school students from previous research articles. The research method used is meta-analysis. The results of the study through the calculating of the t-test and effect size obtained a value of t_hitung = 27,67 > 1,96 = t_tabel which means that the average critical thinking abilty of students with RME is higher than the average critical thinking ability of students with expository learning, so there is a significant inluence between mathematical critical thinking ability of junior high school students who use learning, with a large effect is 2,905 which is included in the interpretation’s category is very large. The implications of this research can be a reference for educators that Realistic Mathematics Education (RME) can improve junior high school students' mathematical critical thinking skills.